Adsorption of some vitamins onto highly disperse silica surface - Vlasova, N. N.; Golovkova, L. P.; Svezhentsova, A. A.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
Adsorption of thiamine (vitamin Bi), riboflavin (B2), and pyridoxine (B6) from aqueous solution onto amorphous silica surface was studied. The investigation of adsorption of tocopherol (vitamin E) and its short-chained analogues from hexane and aqueous micellar solution was performed. Some data on mechanism of vitamin adsorption and structure of adsorption layer were obtained by electron spectroscopy and mass-spectrometry.